2022
DOI: 10.3390/horticulturae8100860
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Exogenous Melatonin Treatment of Table Grape Berry Enhances Quality and Maintains Bioactive Compounds during Refrigerated Storage

Abstract: Table grape berries are classified as a perishable crop that deteriorates quickly after harvest. The application of melatonin after harvest was found to be effective for retarding senescence and slowing ripening. In the current study, we tested the influence of two melatonin concentrations (50 and 100 µmol) as a postharvest application on quality, bioactive compounds, and enzyme activities of grape berries cv “Crimson” stored at 0 ± 1 °C and 90% relative humidity (RH) for 35 days. Our results indicated that me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The outcome of our investigation shows that melatonin administration has a positive impact on the TSS, TA, and total sugar content of preserved fruits and treatment with 0.5 mM melatonin retained the highest content of TSS, TA, and total sugar. Several other researchers have also reported that melatonin administration delayed the decline of TSS during storage (Miranda et al, 2020;Nasser et al, 2022). Similarly, administration of melatonin in strawberries (Liu et al, 2018), pitaya (Ba et al, 2021), kiwi fruit (Wang et al, 2019), jujube (Wang et al, 2022), and citrus navel orange (Ma et al, 2021) during postharvest storage resulted in less degradation of TSS and TA.…”
Section: Tss Titratable Acidity and Total Sugarmentioning
confidence: 85%
“…The outcome of our investigation shows that melatonin administration has a positive impact on the TSS, TA, and total sugar content of preserved fruits and treatment with 0.5 mM melatonin retained the highest content of TSS, TA, and total sugar. Several other researchers have also reported that melatonin administration delayed the decline of TSS during storage (Miranda et al, 2020;Nasser et al, 2022). Similarly, administration of melatonin in strawberries (Liu et al, 2018), pitaya (Ba et al, 2021), kiwi fruit (Wang et al, 2019), jujube (Wang et al, 2022), and citrus navel orange (Ma et al, 2021) during postharvest storage resulted in less degradation of TSS and TA.…”
Section: Tss Titratable Acidity and Total Sugarmentioning
confidence: 85%
“…Medina-Santamarina et al [118] described that the quality parameters of pomegranate fruits like fruit size, color, total acidity, total soluble solids, fruit number per tree, and fruit yield were improved by the application of MT. Nasser et al [128] observed that the increase in transcriptome alterations during the ripening process in grape berries enhanced the quality of berries due to MT treatment. Under drought stress, foliar application of MT enhanced the yield and quality of Moringa oleifera L. in terms of amino acid composition, glutamic acid, and nutrition such as nitrogen, phosphorus, potassium, calcium, and magnesium [129].…”
Section: Melatonin's Role In Crop Yield and Qualitymentioning
confidence: 99%
“…This trend may be attributed to a growing public awareness of the health benefits associated with consuming fresh fruits, such as their provision of bioactive components known for antioxidant and anticancer properties [3] . However, grapes are particularly prone to microbial contamination postharvest, leading to spoilage and potential food safety concerns, which negatively impact their storage longevity and market competitiveness [4] . The issue of postharvest loss is not limited to grapes alone; globally, fruits and vegetables experience loss rates between 28 and 36 %, with rates in China reported as 20–30 % [5] .…”
Section: Introductionmentioning
confidence: 99%